Bronchoalveolar lavage and plasma Antithrombin and cytokines in inhalation and burn injury: a pilot study - Kowal-Vern, Areta (Int J Burns Trauma, 2020)
Systemic inflammatory response syndrome (SIRS) is initiated during the acute phase of thermal injury. The objective was to determine the SIRS impact on cytokine and Antithrombin (AT) levels in smoke inhalation and burn injury. This observational pilot study compared plasma and bronchoalveolar lavage fluid (BAL) cytokine and AT levels in the first six days post smoke inhalation and burn injury. Twenty-five patients, 14 with inhalation + burn injury > 10% total body surface area (TBSA) and 11 with inhalation injury and ≤ 10% TBSA participated. Human Th1/Th2 cytometric bead array kit from BD Biosciences Pharmingen determined cytokine levels; AT levels with Sigma Diagnostics and spectrophotometry. Results indicated no significant age difference between the two groups (42.1 ± 7.2) versus 49.6 ± 6.4 years. On admission, the inhalation group had 5.4 ± 3.9% TBSA compared to 35.0 ± 22.2% TBSA in the inhalation + burn group, P < 0.001. Comparing groups, AT plasma levels were significantly decreased (P = 0.025) and IL-2 levels significantly increased (P = 0.025) in the inhalation + burn group compared to the inhalation group; there was no significant difference in BAL AT or cytokine levels. Combined group plasma AT levels (65.41 ± 4.44%) were significantly increased compared to BAL AT levels (1.06 ± 0.71%), P < 0.001. In contrast, BAL TNF-α levels (35.61 ± 16.01 pg/ml) were significantly increased in relation to the plasma levels (4.68 ± 1.27 pg/ml), P = 0.02. On days 1-2, AT plasma levels were significantly decreased in the inhalation + burn group (41.01 ± 5.24%) compared to the inhalation group (81.02 ± 10.99%), P = 0.002. IL-6 plasma levels were higher in the inhalation + burn group compared to the inhalation group on admission, but both levels decreased by days 3-6. IL-6 BAL levels were elevated in both groups on days 1-2 and decreased by days 3-6. In the first six days of resuscitation, all plasma cytokines were increased in the two groups compared to controls. AT plasma and BAL levels were significantly reduced in both groups, contributing to the coagulopathy. Increased BAL TNF-α and IL-6 levels may have contributed to the pulmonary perturbations during the initial SIRS response in both groups.